Could surgical management improve the IVF outcomes in infertile women with endometrioma?: a review - Hyun Jong Park; Hannah Kim; Geun Ho Lee; Tae Ki Yoon; Woo Sik Lee (Korean Society of Obstetrics and Gynecology, 2019)
Endometriosis is a chronic inflammatory condition that affects fertility and could be toxic to the ovary. Endometrioma per se and surgical interventions for endometrioma significantly reduce the ovarian reserve. Therefore, to prepare for surgical intervention for endometrioma, the high-risk group with decreased ovarian reserve must be considered. There is no evidence to support the use of surgical intervention before in vitro fertilization (IVF) to improve the reproductive outcomes of subsequent IVF in infertile women with advanced-stage endometriosis or endometrioma. As surgical treatment has few benefits, IVF could be recommended immediately for aiding conception in these women. However, the reproductive prognosis of IVF may be worse in the more advanced stages of endometriosis. When dysmenorrhea is severe or when cancer is suspected, surgery prior to IVF may be necessary and justified. When the size of the endometrioma is very large, surgery could be required prior to IVF to facilitate access to follicles during oocyte retrieval or to improve the ovarian response to controlled ovarian stimulation. Prolonged pituitary downregulation in women with surgically diagnosed endometriosis may be helpful to increase the clinical pregnancy rate in subsequent IVF cycles. The purpose of this paper was to review the efficiency and clinical application of the surgical intervention and IVF for infertile women with advanced-stage endometriosis or endometrioma.